Pengaruh efisiensi, efeketivitas, dan kontribusi pajak bumi dan bangunan perdesaan dan perkotaan (PBB P-2) terhadap pendapatan asli daerah (PAD) kota jambi tahun 2019-2023 - Fadila, Nazhira; Kusumastuti, Ratih; Hernando, Riski (Jurnal Akuntansi & Keuangan Unja, 2025)
This study analyzes the impact of efficiency, effectiveness, and the contribution of Rural and Urban Land and Building Tax (PBB P-2) on Regional Original Revenue (PAD) in Jambi City from 2019 to 2023. Using secondary data from BPPRD Jambi and multiple linear regression, results show that efficiency and effectiveness significantly affect PAD, while PBB P-2’s individual contribution is weaker. However, combined, all variables significantly influence PAD. The findings emphasize the importance of improving tax collection efficiency and effectiveness, along with increasing tax contributions, to strengthen local revenue. Better tax management and compliance strategies are recommended to optimize PAD.